Exploring Service Excellence Training: Developing the Professional Competence of Waitstaff at Small-Scale Restaurants in Bali - Saputra, I Nyoman Gede Agus Jaya; Sudiparwati, Putu Ayu; Rusdiarnata, I Ketut; Juniari, Ni Kadek Eni (SIGn Journal of Social Science, 2025)
Small-scale restaurants in tourist destinations confront a dual operational burden. Operators must meet international service quality standards despite limited staffing and operational vulnerability. This study aims to comprehensively explore the sociopsychological dynamics of service excellence training implementation on the transformation of waitstaff competence and its contribution to customer loyalty. Applying an exploratory qualitative approach, this research involved 30 waitstaff classified into novice and senior groups across ten restaurants in Bali. Data collection was executed through in-depth interviews, non-participant observation, and the application of a strict marketing variable isolation protocol. The results showed that the training effectively restored understanding of food service procedures as a means to mitigate operational dysfunction. The role-play simulation method proved capable of eliminating cultural awkwardness by integrating standardized language with local warmth. Furthermore, providing limited autonomy successfully accelerated the customer’s emotion de-escalation phase. Nevertheless, the findings revealed an adaptation disparity. Novice waitstaff demonstrated strong adaptability and learning, whereas senior waitstaff were hindered by entrenched work habits and hierarchical ego. Ultimately, this competency enhancement was shown to increase the guest return visit rate on its own. In conclusion, service excellence training is not merely a technical transfer but an essential strategic driving factor for competitive advantage. This study recommends shifting to tactical daily briefings and positioning senior employees as role models to improve customer retention in the local culinary business ecosystem.